(untitled) (Palíndromo, 2013)
Edgard Aubert De La Rüe (1901-1991) was a Swiss geographer, geologist and photographer. His archive, deposited at the Musée d’Ethnographie de Genève, is a research source to a biographical construction in an artistic research project began in September 2012. Documental sources, together with his scientific works are used as fundament to a literary and visual production, especulating about life, work and methods of the author. De La Rüe was in Brazil, his work about the North-east and its sertão is the focus of this article, where we experiment to observe his interests and compare him to a fictional character through his archivist means and encyclopaedic impulses.